Uji Aktivitas Antibakteri Perasan Jeruk Nipis (Citrus aurantifolia) terhadap Pertumbuhan Bakteri Propionibacterium acnes - Frihendranus, Jeremia Eden; Sianturi, Sister; Erwina, Wiwi (Pharmasipha : Pharmaceutical Journal of Islamic Pharmacy, 2022)
The main causes of skin infections is Propionibacterium acnes. The use of antibiotics can be an effective treatment of acne for example: clindamycin. Lime was a plant that is used as a treatment for acne’s inhibition. The lemon part often used to treat acne was the juice. The purpose of this study was to determine the activity of lime juice in inhibiting the growth of Propionibacterium acnes and to determine the minimum inhibitory concentration of lime juice against Propionibacterium acnes. The study used lime juice with various concentrations of 100%, 50%, 25%, and 12.5% on the growth of Propionibacterium acnes bacteria using the disc diffusion method. The data obtained were tested for normality Kolmogorov-Smirnov and homogeneity test. Then the Kruskall Wallis and Mann-Whiteney test were performed. Based on this study, lime juice was proven to be able to inhibit the growth of Propionibacterium acnes bacteria. The inhibition zone with the highest average concentration was at 100% concentration, which was 18.7 mm and the smallest average inhibition zone was found at a concentration of 12.5%, which was 11.5 mm. The results of the statistical test showed a significant difference with p-value= 0.029 between the positive control and the variation of the sample concentration.